The Biased Therapist: Towards a Gadamerian Analysis (Existential Analysis: Journal of the Society for Existential Analysis, 2008)
This paper explores Gadamer's work on interpretation of texts in chapter four of Truth and Method (Gadamer 2004) and considers how this might be applied to psychotherapy. Hans-Georg Gadamer was a disciple of Martin Heidegger. In his magnum opus, Truth and Method, completed in 1960, he germinates the seed of Heidegger's thinking on philosophical hermeneutics. Gadamer argues that, in order to approach a text in an authentic manner, we need an open and questioning stance, which also acknowledges the existence of our preconceptions. If come to the text in this way, our assumptions shift and we approach the text again from an altered perspective. There is no fixed pre-existing meaning to a text which exists independently of the horizon from which it is viewed. Its meaning can always alter and be seen from a broader perspective. Arguably, this has great relevance for the stance from which we, as psychotherapists, approach our clients. We need to bring ourselves with our own biases into the therapy without attempting to achieve illusory neutrality and allow ourselves to be challenged, as well as challenging. The focus of the therapy will be on the truth or meaning of existence which directly affects us, as opposed to the client's psychology, which does not. This truth is fluid and cannot be predetermined. Such an approach is opposed to general psychological theories and results based therapy.
Keywords: Prejudice; objectivity; hermeneutics; truth; understanding; horizon; therapeutic stance